Redescription of the final stadium larva of Megalestes heros Needham from Fujian, China, with discussion of the characters of genus Megalestes Selys (Odonata: Zygoptera: Synlestidae) - Xu, Qi-Han (Zootaxa, 2020)
The final stadium larva of Megalestes heros Needham, 1930 is redescribed and illustrated in detail. It is characterized by having a long and cylindrical body, a very long prementum with two end hooks of unequal size on lateral lobe, parallel wing sheaths, long and slender legs, female ovipositor short reaching the basal third of S10, and based on a distinct abdominal color pattern. The major diagnostic characters of the larvae of the genus Megalestes are as follows: (1) body smooth and slender, with long abdomen and leaf-shaped caudal gills; (2) antenna filiform, seven-segmented,third segment longest; (3) median cleft present in median lobe of prementum; lateral lobe with two end hooks of unequal size, the inner one being longer and larger than the outer, movable hook without setae; (4) wing sheaths parallel to each other.